Overview of oral cancer in the state of Paraná, Brazil: an epidemiological analysis of the period 2008-2019 - Martina Bordin, Giuliana (2022)
Objective: to analyze the panorama of oral cancer in adults in the state of Paraná, from 2008 to 2019. Methods: descriptive, population-based study in the state of Paraná, Brazil, with analysis of secondary data obtained from the federal databases of the Hospital Information System. The variables investigated were: frequency of hospitalization, geographic distribution, deaths by sex, race/color, age group and hospitalization costs. Data were tabulated in TabWin 4.15 and analyzed in Microsoft Excel®. Results: there was an increase in oral neoplasms from 2017, especially in the East and Northwest regions. The frequency of oral cancer in men was 64% higher than in women, with the age of 45 years being the most affected. In men, higher values occurred between 55 and 64 years of age (31.3%), while in women from 65 years of age (37.2%). Conclusion: cases of oral cancer are distributed throughout the state, revealing the importance of adopting a global prevention program and application of early diagnosis and treatment methods.